Business Ethics is a Matter of Good Conduct and of Good Conscience? - Galavielle, Jean-Pierre (Journal of business ethics, 2004)
The myth of an economy where nobody could have a predominant position, has lost its credibility. The presentiment of a high risk of social explosion makes companies undertake tentative moral legitimation. Thus, a new paradigm develops according to which the firm has to care for the satisfaction of public interest if “it wants to try to win forgiveness” for misbehavior towards the decorum rules of the atomicity of competition. Thus, there is a wave of “business ethics industry” building up. However, the stock exchange performances considered as ethical, are not different from others! The market does not seem to be able to say why it might be interesting to invest in stock considered as ethical. Moreover, opinion polls reveal a very significant discrepancy between the characterization of “the responsible company” as defined by itself or by notation agencies and, on the other hand, the hierarchy of criteria according to the answers of polled people. When companies and agencies favor sustainable development and good governance, rejecting child labor and so on, polled people consider that the paramount criterion of ethical conduct is personnel management. The problem is right here. Such is the view of a positively critical economist, situated at the point where macroeconomics meets corporate management.